Religion's influence on U.S. foreign policy: a literature assessment - Muhammad Nur Rahmat Bin Abdul Mutalib (Nanyang Technological University, 2023)
This dissertation will review the literature pertaining to religion and United States (U.S.) foreign policy, discuss its limitations, and propose some new avenues for future research. In it, I assess a range of works addressing religion’s role within the study of International Relations (IR), religion as a source of interstate conflict, religion’s influence in the U.S.-Israeli bilateral relationship, and religion’s effect on American public opinion relating to U.S. foreign policy. To advance the literature on religion and U.S. foreign policy, I propose two promising avenues. The first is the direct influence of the religious beliefs of U.S. Presidents and policymakers on U.S. foreign policy decision making. The second is how the religious identity of another country shapes U.S. foreign policy towards it. While IR scholars still hold contending perspectives towards religion, I conclude that the field has made significant progress over the past four decades on the grounds that religion is no longer taboo in IR, scholars are no longer averse to attributing religion as a causal variable behind international phenomena, and even detractors of religion acknowledge that it has a role in shaping a country’s societal norms and traditions which in turn affects its foreign policy behavior.